2014
DOI: 10.5114/aoms.2014.46212
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions in hospitalized patients with chronic heart failure and chronic obstructive pulmonary disease

Abstract: IntroductionPolypharmacy is common in patients with chronic heart failure (HF) and/or chronic obstructive pulmonary disease (COPD), but little is known about the prevalence and significance of drug-drug interactions (DDIs). This study evaluates DDIs in hospitalized patients.Material and methodsWe retrospectively screened medical charts over a 6-month period for diagnosis of chronic HF and/or COPD. Potential DDIs were evaluated using Lexi-Interact software.ResultsSeven hundred and seventy-eight patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 41 publications
4
35
1
Order By: Relevance
“…7,22,31,33 In our study PR for exposure to potentially relevant pDDIs in patients with higher number of drugs ranged from 3.07 up to 25.20, compared to 1-3 drugs as a reference category. The highest PR values were calculated for D class exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,22,31,33 In our study PR for exposure to potentially relevant pDDIs in patients with higher number of drugs ranged from 3.07 up to 25.20, compared to 1-3 drugs as a reference category. The highest PR values were calculated for D class exposure.…”
Section: Discussionmentioning
confidence: 99%
“…20 Other studies conducted on the cardiology ward, reported DDI and drug-food interactions frequency altogether or assessed only DDIs in the heart failure patients. 21,22 The potential of using supporting electronic systems to manage pDDIs in CVD patients was not assessed. In this regard, the aim of the study was to describe the type and prevalence of potentially relevant pDDIs in CVD patients, and to assess the concurrent exposure to additional risk factors such as renal or liver disease, which may further affect drug exposure and therapy outcomes.…”
mentioning
confidence: 99%
“…Drug–drug interactions (DDIs) are common causes of preventable adverse drug events (ADEs), in which the effects of one drug are changed by the presence of another one. The outcome can be harmful if the interaction causes an increase in the toxicity or decrease in the efficacy of a drug . Polypharmacy (the use of 4 or more medications by a patient) has been identified as a major risk factor for the occurrence of ADEs related to potential drug–drug interactions (pDDIs) …”
mentioning
confidence: 99%
“…(24) In clinical practice, guideline based (poly) pharmacy due to several chronic conditions gives perfect ground to drug-drug interactions. (25) Even very simple systems can be helpful, and it generally holds true that physicians with training in geriatrics are less likely to prescribe potentially inappropriate medications. (26,27) These issues need to be given first line priority by the decision makers to allow adequate development of geriatric medicine at all levels of a health care system.…”
Section: Management After Icu Dis-chargementioning
confidence: 99%